Combination of Matrix Simple Additive Weighting Algorithm (SAW) on the Reference URICA-Scale to Measure Readiness for Change in Narcotic Rehabilitation Patients - Soni Adiyono; Rahmat Gernowo; Adi Wibowo (Universitas Aisyah Pringsewu, 2022)
This study aims to design a matrix combination in the URICA-Scale calculation and the simple additive weighting (SAW) method that can be used as a measuring tool to evaluate the readiness of drug rehabilitation patients using the University of Rhode Change Assessment Scale (URICA-Scale) as a desire combined with simple additive weighting (SAW) method in order to facilitate the design of electronic information systems regarding assessment tests with reference to URICA-Scale. In software development, the design modeling step in the system is one part of the (System Development Life Cycle) contained in the Waterfall model. The results of this study are able to provide an arrangement of calculation matrices where the combination of these matrices contributes to programmers in implementing them into certain programming languages. Abstrak: Penelitian ini bertujuan untuk merancang desain kombinasi matriks pada perhitungan URICA-Scale dan metode simple additive weighting (SAW) yang dapat digunakan sebagai alat ukur guna mengevauasi tentang kesiapan pasien rehabilitasi narkotika dengan menggunakan University of Rhode Change Assesment Scale (URICA-Scale) sebagai acuan yang dikombinasikan dengan metode simple additive weighting (SAW) agar dapat mempermudah dalam merancang sistem informasi elektronik mengenai tes asesmen dengan acuan URICA-Scale. Dalam pengembangan perangkat lunak langkah pemodelan desain pada sistem merupakan salah satu bagian dari (System Development Life Cycle) yang terdapat pada model Waterfall. Hasil penelitian ini mampu memberikan susunan matrix perhitungan dimana dengan adanya gabungan dari matriks tersebut memberikan kontribusi bagi programmer dalam melakukan implementasi kedalam Bahasa pemrograman tertentu.